Gene Dosage–Dependent Association of DYRK1A With the Cytoskeleton in the Brain and Lymphocytes of Down Syndrome Patients - Dowjat, Karol; Adayev, Tatyana; Kaczmarski, Wojciech; Wegiel, Jerzy; Hwang, Yu-Wen (Journal of neuropathology and experimental neurology, 2012)
ABSTRACTThe triplication of the DYRK1A gene encoding proline-directed serine/threonine kinase and located in the critical region of Down syndrome (DS) has been implicated in cognitive deficits and intellectual disability of individuals with DS. We investigated the effect of abnormal levels of this kinase on the cytoskeleton in brain and peripheral tissues of DS subjects. In DS tissues, the predictable approximately equal to 1.5-fold enhancement of the levels of DYRK1A protein was demonstrated. An association of DYRK1A with all 3 major cytoskeleton networks was identified using immunoprecipitation. We concentrated on the actin cytoskeleton because its association with DYRK1A was the most affected by the enzyme levels. As measured by coimmunoprecipitation in DS tissues, but not in fragile X lymphocytes, actin association with DYRK1A was reduced. This reduced association was dependent on the state of phosphorylation of cytoskeletal proteins and was present only in cells overproducing DYRK1A kinase; therefore, the effect was attributable to the DYRK1A gene dosage. Alterations of DYRK1A-actin assemblies were detected in newborn and infant groups, thereby linking DYRK1A overexpression with abnormal brain development of DS children. The identification of the actin cytoskeleton as one of cellular targets of DYRK1A action provides new insights into a gene dosage–sensitive mechanism by which DYRK1A could contribute to the pathogenesis of DS. In addition, the presence of this DS-specific cytoskeleton anomaly in lymphocytes attests to the systemic nature of some features of DS. To our knowledge, this is the first study conducted in human tissue that shows DYRK1A association with the cytoskeleton.